Connected learning in and after school: Exploring technology's role in the learning experiences of diverse high school students. Issue 2 (14th March 2016) - Davis, Katie; Fullerton, Sean
ABSTRACT: This article explores the efforts of one network of afterschool programs to leverage new media technologies to promote out-of-school learning among high school students from nondominant backgrounds and connect this learning to their school contexts. The study entailed in-depth interviews and focus groups with 40 youth and adults involved in the afterschool programming, as well as 12 observations of afterschool sessions and school-based classes. A thematic analysis of the transcripts and field notes revealed a notable discrepancy in youth's learning experiences in school and afterschool settings. Out-of-school learning experiences were more likely to be peer supported, interest powered, and production centered. They were also more likely to engage youth and adults around a shared purpose and to take advantage of openly networked infrastructures. Two theoretical frameworks from the field of information behavior are used to explore the distinct successes and challenges associated with promoting rich learning experiences in each setting.